2018
DOI: 10.1177/0036933018760761
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of emergency department presentations following novel psychoactive substance use

Abstract: Background and aims Novel psychoactive substances are compounds intended to mimic the effects of illicit drugs. They provide a unique challenge to healthcare, as complications of their use and their impact on services are relatively unknown. This study aims to determine nature of presentations, patient demographics and impact on healthcare. Methods Novel psychoactive substances users who presented to a large urban emergency department over 4 weeks were prospectively identified and followed for 1 year. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Since there may well be further information available on both the deep web and the dark net, future studies of our group will be focussing on expanding drug searches on these less accessible areas of the web. NPS.Finder‐based studies will need to focus as well on further languages, which should include: Chinese, Japanese and Arabic, since previous studies have highlighted their importance in NPS‐based studies . Furthermore, from a formal point of view the current literature review would not be considered as systematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there may well be further information available on both the deep web and the dark net, future studies of our group will be focussing on expanding drug searches on these less accessible areas of the web. NPS.Finder‐based studies will need to focus as well on further languages, which should include: Chinese, Japanese and Arabic, since previous studies have highlighted their importance in NPS‐based studies . Furthermore, from a formal point of view the current literature review would not be considered as systematic.…”
Section: Discussionmentioning
confidence: 99%
“…NPS.Finder-based studies will need to focus as well on further languages, which should include: Chinese, Japanese and Arabic, since previous studies have highlighted their importance in NPS-based studies. 98 Furthermore, from a formal point of view the current literature review would not be considered as systematic. Instead, it was conceived as a literature overview, focussing on the cathinone clinical issues of interest.…”
Section: Limitationsmentioning
confidence: 99%
“…Henshall et al [22] in 2015 reported that the average age of hospitalized patients using NPS was 33 years; the youngest was 17 and the oldest 57. Most of the patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the more immediate consequences of NPS use are evident in the prisons system and in admissions to hospital accident and emergency departments for acute intoxication (Liakoni, Dolder, Rentsch, & Liechti, ; Ralphs, Williams, Ashew, & Norton, ). These harmful consequences are particularly associated with people who are homeless (Henshall et al, ). The impact of NPS use on mortality and morbidity, both medium and long‐term has yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%